Effects of COVID-19 on variations of taxpayers in tourism-reliant regions: The case of the Mexican Caribbean - Oliver Cruz-Milan; Sergio Lagunas-Puls (Journal of Risk and Financial Management, 2021)
Given the tourism industry's risk and vulnerability to pandemics and the need to better understand the impacts on tourism destinations, this research assesses the effect of the COVID-19 outbreak on the variation of taxpayer units in the Mexican Caribbean region, which includes some of the major sun-and-sand beach destinations in Latin America. Using monthly data of registered taxpayer entities at the state and national levels as the analysis variable, probability distributions and definite integrals are employed to determine variations of the year following the lockdown, compared with previous years' data. Results indicate that despite the government's measures to restrict businesses' operations and a reduction in tourism activities, registered taxpayers at the regional level did not decrease for most of 2020. Further, as business activities and tourism recovered, taxpayer units increased at the end of 2020 and beginning of 2021. Surprisingly, such a pattern was not observed at the national level, which yielded no statistically significant variations. A discussion of factors influencing the resilience of the tourism region in the study (e.g., outbound markets' geographic proximity, absence of travel restrictions, closure of competing destinations) and implications for public finances are presented.
Keywords: 330; COVID-19; taxpayer entities; economic risk; tourism recovery; fiscal revenues; crisis; resilience; tourism destinations; Mexico; Quintana Roo; Mexican Caribbean